CMAC and its extensions for efficient system modelling - Szabó, Tamás; Horváth, Gábor (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with the family of CMAC neural networks. The most important properties of this family are the extremely fast learning capability and a special architecture that makes effective digital hardware implementation possible. The paper gives an overview of the classical binary CMAC, shows the limitations of its modelling capability, gives a critical survey of its different extensions and suggests two further modifications.
Keywords: CMAC; neural networks; B-splines; hardware implementation